2021
DOI: 10.1101/2021.06.02.21258203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The INDSCI-SIM model for COVID-19 in India

Abstract: Estimating the burden of COVID-19 in India is difficult because the extent to which cases and deaths have been undercounted is hard to assess. The INDSCI-SIM model is a 9-component, age-stratified, contact-structured compartmental model for COVID-19 spread in India. We use INDSCI-SIM, together with Bayesian methods, to obtain optimal fits to reported cases and deaths across the span of the first wave of the Indian pandemic, over the period Jan 30, 2020 to Feb 15, 2021. We account for lock-downs and other non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 97 publications
(95 reference statements)
1
5
0
Order By: Relevance
“…Higher number of filled grains/panicle (76.47), test weight (29.93 g), seed yield (2.95 t/ha), straw yield (6.70 t/ha) and biological yield (9.63 t/ha) were obtained with application of borax @ 10 kg/ ha. The findings were in accordance with the study reported by Hazra and Sinha (1996) and Khanday et al (2009). No significant interaction was found between ZnSO 4 and borax on yield components of oats.…”
Section: Yield Components and Yieldsupporting
confidence: 93%
“…Higher number of filled grains/panicle (76.47), test weight (29.93 g), seed yield (2.95 t/ha), straw yield (6.70 t/ha) and biological yield (9.63 t/ha) were obtained with application of borax @ 10 kg/ ha. The findings were in accordance with the study reported by Hazra and Sinha (1996) and Khanday et al (2009). No significant interaction was found between ZnSO 4 and borax on yield components of oats.…”
Section: Yield Components and Yieldsupporting
confidence: 93%
“…The rates and parameters used were derived from Kerr et al [ 33 ] and are presented in S4 and S5 Tables. We simulated the spread of COVID-19 (as a model for a respiratory disease) using the compartmental model described by Hazra et al [ 34 ] ( S10 Fig ) in the population in order to track differences in the spread of the infection due to the seasons.…”
Section: Methodsmentioning
confidence: 99%
“…We have used parameter values from the INDSCI-SIM model. 25 The population is divided into age bands grouped into 10-year intervals: 0-9, 10-19, 20-29, 30-39, 40-49, 50-59, 60-69, 70-79, and 80+ years. Contacts between different age bands are differential, reflecting the social structure of the population.…”
Section: Modelmentioning
confidence: 99%
“…We use contact matrices that are a weighted average over the contributions from different types of "locations" (e.g., home, workplace, school). 25,30 The weights may vary with time, appropriate to the interventions implemented at that point in time, and are described in Table 4.…”
Section: Reopening Schoolsmentioning
confidence: 99%